An overview of solutions to overcome illegal hawking in Shah Alam / Athirah Che Abu Bakar, Azza Azmi, Dona Liyanna Sabariah Azmi - Che Abu Bakar, Athirah; Azmi, Azza; Azmi, Dona Liyanna Sabariah (2007)
This legal research is conducted with an aim to study and analyse the solutions available to overcome illegal hawking in Shah Alam. Specific legislations had been enacted to govern the hawkers. Measures also had been taken by the local authority to reduce the problem. Despite that, illegal hawking still exists. Thus, this research will focus on the flaws and the weaknesses on the current by-laws pertaining to the issues of illegal hawking apart from other factors. The scope of this legal research is on the legislations on hawking as applied in Shah Alam, Selangor. Besides that, a comparative study has been made with Singapore. This legal research will be based on the secondary sources from the Law Library of Universiti Teknologi Mara (UiTM). Legislation, newspaper articles, cases and other appropriate sources that relates to hawking are also used. Besides, unstructured interviews and surveys were conducted to gather information and views from the government officers, hawkers; illegal or otherwise in regards of hawking. It is hoped that this legal research will provide a comprehensive discussion on illegal hawking in Shah Alam and proposed amendments or suggestion to the current by-laws to overcome illegal hawking.